2008
DOI: 10.1007/s10753-008-9096-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Baicalin and Octreotide on NF-κB and P-Selectin Expression in Liver and Kidney of Rats with Severe Acute Pancreatitis

Abstract: To observe the influence of Baicalin and Octreotide on liver and kidney of rats with severe acute pancreatitis (SAP) and discuss the related mechanism. SAP rats were randomly divided into model control, Baicalin treated and Octreotide treated group (n = 45). The same number of normal rats were included in sham-operated group (n = 45). In all groups, the mortality rate, pathological changes as well as expression levels of NF-kappaB p65 and P-selectin protein in liver and kidney were observed at 3, 6 and 12 h af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…The present study showed that both Baicalin and Octreotide could lower the levels of endotoxin and TNF-α in blood, regulate the expression of Bax protein, induce apoptosis of multiple organs, and facilitate the recovery of multiple organ injury [46][47][48]. We think that Baicalin may share a similar mechanism to that of Octreotide, which is associated with inhibiting endotoxin and TNF-α in blood to block the excessive inflammatory reaction, and inducing apoptosis in multiple organs [16][17][18][19].…”
Section: Discussionmentioning
confidence: 88%
“…The present study showed that both Baicalin and Octreotide could lower the levels of endotoxin and TNF-α in blood, regulate the expression of Bax protein, induce apoptosis of multiple organs, and facilitate the recovery of multiple organ injury [46][47][48]. We think that Baicalin may share a similar mechanism to that of Octreotide, which is associated with inhibiting endotoxin and TNF-α in blood to block the excessive inflammatory reaction, and inducing apoptosis in multiple organs [16][17][18][19].…”
Section: Discussionmentioning
confidence: 88%
“…For example, baicalin has multiple functions including anti-bacterial and anti-inflammatory activities, as well as clearing free oxygen radicals and decreasing the production of endotoxin and ultimately alleviating reperfusion injury in ischemic tissues [41]. Baicalin inhibits IL1b-induced matrix metalloproteinase-1/tissue inhibitors of metalloproteinase-1 expression in periodontal ligament cells [42].…”
Section: Discussionmentioning
confidence: 99%
“…The investigators independently screened all articles for those that met broad inclusion criteria. A total of 92 citations were found [1,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,…”
Section: Literature Searchmentioning
confidence: 99%